2013
DOI: 10.1186/1479-5876-11-297
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodelling component SMARCB1/INI1 influences the metastatic behavior of colorectal cancer through a gene signature mapping to chromosome 22

Abstract: BackgroundINI1 (Integrase interactor 1), also known as SMARCB1, is the most studied subunit of chromatin remodelling complexes. Its role in colorectal tumorigenesis is not known.MethodsWe examined SMARCB1/INI1 protein expression in 134 cases of colorectal cancer (CRC) and 60 matched normal mucosa by using tissue microarrays and western blot and categorized the results according to mismatch repair status (MMR), CpG island methylator phenotype, biomarkers of tumor differentiation CDX2, CK20, vimentin and p53. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Loss of expression of SMARCB1 has been reported in colorectal adenocarcinomas and has been associated with higher histological grade, larger tumor size, poor overall survival, MSI, and the BRAF V600E mutation (Wang et al , ). Another CRC study has reported low expression of SMARCB1 to associate with poor differentiation, liver metastasis, and poorer survival regardless of the MMR status or tumor stage (Pancione et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of expression of SMARCB1 has been reported in colorectal adenocarcinomas and has been associated with higher histological grade, larger tumor size, poor overall survival, MSI, and the BRAF V600E mutation (Wang et al , ). Another CRC study has reported low expression of SMARCB1 to associate with poor differentiation, liver metastasis, and poorer survival regardless of the MMR status or tumor stage (Pancione et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…An independent cohort, named as validation series II consisting of 140 stage I-IV primary CRCs collected consecutively was then evaluated [ 21 , 22 ]. They represented a continuous, unselected TMAs cohort of patients with molecular, histopathological and clinical findings (OS) recruited during the period 2003–2009.…”
Section: Methodsmentioning
confidence: 99%
“…The gene-specific copy number was calculated according to the standard curve and normalized to the amount of cDNA (ng) in the reaction. All PCR reactions were performed in triplicate and expression levels were computed as reported [ 20 , 21 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…MUC2, MUC5AC, and MUC6 [51]. Furthermore, loss of CDX2 expression was associated with decreased expression of SMARCB1/ INI1 À a subunit of the chromatin remodeling complex À which might lead to change in transcription of several genes [53]. …”
Section: Right Versus Left Sided Tumorsmentioning
confidence: 99%